Manipulation of Long-Distance femtosecond laser Filamentation: From physical model to acoustic diagnosis. (January 2023) - Shang, Binpeng; Qi, Pengfei; Guo, Jiewei; Zhang, Zhi; Guo, Lanjun; Chu, Chunyue; Liu, Jinpei; Kosareva, Olga G.; Zhang, Nan; Lin, Lie; Liu, Weiwei
Highlights: Acoustic method was adopted to quantitatively measure the long-distance filamentation. A simple physical model was presented to analyze the spatial distribution of filament. The onset and length of filament can be conveniently obtained from the model. The increase of the filament length can be obtained for longer pulse with more energy. Abstract: The promising application of femtosecond laser filamentation in atmospheric remote sensing brings imperative demand for diagnosing and controlling the spatiotemporal dynamics of long-distance filamentation. Here, the acoustic method was adopted to quantitatively diagnose the long-distance filamentation of femtosecond pulses manipulated by energy and temporal domain. The onset and length of filament can be conveniently obtained from a simple analytic formula based on reasonable approximation and further demonstrated by the experimental results. The influence of pulse energy and initial pulse chirp under three different focal lengths (∼10 m, 20 m, and 30 m) on the filamentation in the air were studied experimentally. These findings provide a guiding significance for the optimal control of the long-distance propagation of filament, thereby laying a firm foundation for femtosecond laser-based atmospheric remote sensing.